2004
DOI: 10.1073/pnas.0405353101
|View full text |Cite
|
Sign up to set email alerts
|

Sfp1 is a stress- and nutrient-sensitive regulator of ribosomal protein gene expression

Abstract: Yeast cells modulate their protein synthesis capacity in response to physiological needs through the transcriptional control of ribosomal protein (RP) genes. Here we demonstrate that the transcription factor Sfp1, previously shown to play a role in the control of cell size, regulates RP gene expression in response to nutrients and stress. Under optimal growth conditions, Sfp1 is localized to the nucleus, bound to the promoters of RP genes, and helps promote RP gene expression. In response to inhibition of targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
391
3
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(418 citation statements)
references
References 51 publications
20
391
3
4
Order By: Relevance
“…It was reported that PKA promotes nuclear localization and binding of the transcriptional activator Sfp1 to the promoters of ribosomal protein genes (Marion et al 2004). In addition, PKA appears to induce transcription of ribosomal protein genes also by inhibition of Yak1, which in turn is required to promote the activity of the transcriptional corepressor Crf1 ).…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that PKA promotes nuclear localization and binding of the transcriptional activator Sfp1 to the promoters of ribosomal protein genes (Marion et al 2004). In addition, PKA appears to induce transcription of ribosomal protein genes also by inhibition of Yak1, which in turn is required to promote the activity of the transcriptional corepressor Crf1 ).…”
Section: Regulation Of the Camp-pka Pathwaymentioning
confidence: 99%
“…TORC1 regulates, probably via direct phosphorylation, the nucleocytoplasmic distribution and the promoter binding of Sfp1. In exponentially growing cells, Sfp1 is localized in the nucleus where it promotes both RP as well as Ribi gene expression, but upon TORC1 inactivation Sfp1 translocates to the cytoplasm (Jorgensen et al 2004;Marion et al 2004;Lempiainen et al 2009). Sfp1, in turn, appears to affect the localization of the Fhl1-Ifh1 complex.…”
Section: Rapamycin-sensitive Signalling Via Torc1mentioning
confidence: 99%
“…The TOR-RAS-PKA branch also regulates the localization of the stress-responsive transcription factor Sfp1, which activates the RP and ribosome biogenesis regulons to promote ribosome synthesis in parallel to Sch9. Sfp1 is mainly nuclear under normal growth conditions but dislodges nuclear FHL1 and IFH1 under different stress treatments to repress cell growth (Jorgensen et al, 2004;Marion et al, 2004). Whether a similar mechanism operates in mammals is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The forkhead-like protein Fhl1 and an interacting factor Ifh1 constitute one axis of RP gene regulation Schawalder et al, 2004;Wade et al, 2004;Rudra et al, 2005). A second regulator that localizes to RP gene promoters is the split Zn-finger transcription factor Sfp1 (Fingerman et al, 2003;Jorgensen et al, 2004;Marion et al, 2004). RP gene expression is regulated by PKA through both Fhl1 and Sfp1 (Jorgensen et al, 2004).…”
mentioning
confidence: 99%